Nutritional status of U.S. elite heptathletes - Houtkooper, L. B. M; Mullins, V. A.; Taylor, A.; Poole, C. (1998)
The purposes of this study were to continue and to expand the nutritional assessment program of the elite U.S. Heptathlete Development Project. The objectives of this study were to: - conduct initial and/or one year follow-up assessments of selected dietary, clinical, and biochemical components of the nutritional status of elite U.S. heptathletes during training and competition. - provide assistance to these athletes for development of the dietary component of their training and competition programs in order to improve or maintain desirable nutritional status. PARTICIPANTS The participants in this study were nine U.S. elite heptathletes and four Jr. heptathletes who agreed to take part in this Development Project. Eleven athletes had participated in this project in prior years and two were new to the project in 1997. Three of the athletes participated in both the competition and training portions of the project. All reports of results from assessments for each athlete identify the athletes only by individual identification numbers and not by names. METHODS Nutritional status assessments conducted in this study included dietary intake during training and/or competition, clinical body composition measurements, and biochemical analyses of blood samples. Participation in all aspects of the Development Project was voluntary. All athletes completed written consent forms approved by the University of Arizona Ethical Review Committee. National Championships Three athletes participated in the nutritional status assessment at the National Championships in Indianapolis in June. Each athlete was provided with nutrition guidelines and planning forms to help them design and schedule fluid and food intake during the two days of competition at the Championships (Attachment A). Summit Meeting Thirteen athletes participated in one or more aspects of the nutritional assessments conducted at the Summit Meeting in November at the ARCO Olympic Training Center in Chula Vista California. This report summarizes the results of the nutritional assessments conducted as part of the Summit Meeting.